A Case Report on a Dead Man Walking in a Rural University of South Africa - BL MEEL (Indian Journal of Forensic Medicine & Toxicology, 2022)
Background: Abuse of power in rural universitiesis less visible to the public but widely prevalent.Myriad formsofcorruption are prevalent in the rural university concerned. Productive staff is generallyappreciated and awarded inmost universities but in this rural university, they get punished, terminated, or subjected to disciplinary inquiries.Objective: To report on the abuse of power and difficultiesof an academic in a rural university of south Africa.Case History: X was an employee of the department of health and affiliated with the local University in a dualsystem of employment where he has served the university for over two decades (1996 to 2018). He underwentpersistent harassment, bullying,and dehumanization in his early period of employment. It progressively evolvedtoa more serious form with disciplinary inquiries, suspension, stoppage of salary, and birthday bonus. Themanagers of this rural university tried hard repeatedly to carry out constructive termination but failed. Mr. Xretired after his completion of age 65 with respect and appreciation. The history, duration, and different designs ofabuse of power havebeen described in this report.Conclusion: It isguilty, to be honest, and hardworking in a rural university in South Africa as it functions like asecretive society.